2016
DOI: 10.1017/ice.2016.149
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Antimicrobial Stewardship at Solid Organ and Hematopoietic Cell Transplant Centers in the United States

Abstract: Objective To assess the extent of antimicrobial stewardship programs (ASPs) at solid organ (SOT) and hematopoietic cell transplant (HCT) centers in the United States (US). Design An 18-item voluntary survey was developed by Memorial Sloan Kettering Cancer Center and University of Miami to gauge current antimicrobial stewardship practices in transplant patients, examine the availability and perceived usefulness of novel diagnostics and azole levels to guide therapy, and identify challenges for implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
103
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 27 publications
1
103
0
1
Order By: Relevance
“…1 A recent US survey of adult and pediatric transplant centers found that monitoring is not done robustly in HCT or SOT patients despite the presence of an ASP with the exception of Clostridium difficile rates, followed by antimicrobial costs. 107 Because prescribing of antifungal agents is disproportionately high for transplant (and other highly immunocompromised) patients, efforts to examine whether antifungal stewardship interventions are effective in these patients should be encouraged. While standards have not been established regarding the frequency of monitoring, it seems reasonable to monitor an ASP's clinical impact at least annually with more frequent assessments depending on programmatic needs.…”
Section: Thinking About Metricsmentioning
confidence: 99%
“…1 A recent US survey of adult and pediatric transplant centers found that monitoring is not done robustly in HCT or SOT patients despite the presence of an ASP with the exception of Clostridium difficile rates, followed by antimicrobial costs. 107 Because prescribing of antifungal agents is disproportionately high for transplant (and other highly immunocompromised) patients, efforts to examine whether antifungal stewardship interventions are effective in these patients should be encouraged. While standards have not been established regarding the frequency of monitoring, it seems reasonable to monitor an ASP's clinical impact at least annually with more frequent assessments depending on programmatic needs.…”
Section: Thinking About Metricsmentioning
confidence: 99%
“…(4). Over the past few decades, published literature related to safety and efficacy of antibiotic stewardship strategies in high-risk immunocompromised hosts such as SOT recipients and those with hematologic malignancies exposed to cytotoxic chemotherapy and prolonged neutropenia is limited (8).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a dramatic reduction in the development of antimicrobial agents with novel mechanisms of action to combat the rising spread of infections caused MDR organisms, although implementation challenges in immunocompromised hosts have been described (4,8). In general, antimicrobial-stewardship programs (ASPs) can help to improve clinical outcomes, limit antibiotic resistance and reduce medical costs by limiting the inappropriate use of antimicrobials in hospitals (1,3,10).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations